STRATEGI DAN PROGRAM EKSPOR PRODUK KERANJANG ANYAMAN BAMBU “KALATHI APO BAMPOU” KE PASAR ASEAN - Nadila Putri Maharani; Eny Setyowati (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2023)
The Campus Merdeka Certified Internship Program (MBKM) is an initiative by the Ministry of Education and Culture (KEMENDIKBUD) that provides opportunities for students to gain experience through internships and independent studies. Through this program, students can sharpen skills relevant to their field of study through real projects and obtain certificates as evidence of their achieved competencies. The National Export School Foundation collaboratesin the Independent Study with Certification program under the Campus Merdeka Certified Internship Program (MBKM), which focuses on the theme "Be A Digital Exporter" for students across Indonesia. This program involves collaboration between students and the micro, small, and medium-sized bamboo weaving business "Bambu To Bambu" in Gunung Kidul, Yogyakarta. Through mentoring and provided materials, students contribute to enhancing the products of these micro, small, and medium-sized enterprises (UMKM) through branding, packaging,and digital marketing, thereby helping them improve their export capabilities and understand the potentialof local export products and their interactions with the global market. The program is expected to assist thesemicro, small, and medium-sized enterprises (UMKM) in preparing and successfully marketing their products in the international market.